Anti-migration and Anti-invasion Effects of Mitragyna Speciosa Polar Extract on A549 Cell - Phoonket, Sasis; Yisarakun, Waranurin; Srikoon, Pattaravadee; Poolpol, Kulwara (Trends in Sciences, 2025)
Mitragyna speciosa (commonly known as Kratom) is a tropical plant native to Southeast Asia and a member of the Rubiaceae family. This study aimed to investigate the anticancer potential of crude M. speciosa leaf extracts against non-small cell lung cancer (NSCLC) cells. Dried leaves were extracted using 95% ethanol or 95% methanol at a 1:10 w/v ratio via maceration. The cytotoxic effects of the extracts were evaluated using the MTT assay, and results were expressed as IC50 values. Cell migration and invasion were assessed using wound healing and Transwell invasion assays, respectively. All experiments were conducted in triplicate. The MTT assay revealed that both ethanolic and methanolic extracts significantly reduced the viability of A549 cells in a dose-dependent manner. The methanolic extract exhibited greater potency, with an IC50 of 283 µg/mL, compared to 295 µg/mL for the ethanolic extract. In the wound healing assay, both extracts inhibited A549 cell migration, with the methanolic extract showing stronger suppression at concentrations of 50, 100, and 250 µg/mL. The ethanolic extract also reduced migration but required higher concentrations to achieve similar effects. Transwell invasion assay results further demonstrated that both extracts suppressed cell invasion, with the methanolic extract being more effective at lower concentrations (50 and 100 µg/mL). Furthermore, real-time RT-PCR analysis revealed that the extracts upregulated E-cadherin and, in the methanolic group, downregulated MMP-2 expression, suggesting suppression of epithelial-mesenchymal transition (EMT)-associated invasion. These findings highlight the potential of M. speciosa as a source of bioactive compounds with anti-migratory and anti-invasive properties. Further investigation is warranted to elucidate the underlying mechanisms and evaluate its potential for development as a natural anticancer agent. HIGHLIGHTS This study investigates anti-metastatic effects of Mitragyna speciosa extract on NSCLC cell. The methanolic extract demonstrated higher efficacy compared to the ethanolic extract. The extract modulates key signaling pathways related to cancer metastasis. Findings suggest potential therapeutic implications for lung cancer treatment. GRAPHICAL ABSTRACT